Improving Microstructural Homogeneity of Investment-Cast Single-Crystalline Ni-Base Superalloys by Using Fluidized Carbon Bed Cooling - Schulze, Hannes; Zenk, Christopher; Körner, Carolin (Advanced Engineering Materials, 2024)
One impeding factor for faster solidification in typical investment casting processes is the limited heat removal capability. This study compares the classical Bridgman technique and the fluidized carbon bed cooling (FCBC) casting method. In particular, the influence of the thermal design is investigated in terms of microstructural and compositional homogeneity in single-crystalline CMSX-4. These investment casting processes mainly differ in the baffle type used to insulate the hot and cold zones inside of the casting vessel. While the Bridgman process is based on radiation cooling, the FCBC casting process relies on a dynamic baffle made of expanded graphite that is buoyant on fluidized bed of glassy carbon beads. Such a dynamic insulation layer can adapt to the cross-sectional variation of ceramic shell molds and provide a better thermal insulation, which results in more uniform solidification conditions. This enables a reduction in the primary dendrite arm spacing by up to 26%, an increase in the homogeneity of the microstructure and composition, as well as a reduction in overall porosity and mean pore size of 41%.
CRIS-Team Scopus Importer:2024-05-03
Keywords: evaporation; fluidized carbon bed cooling; homogeneities; investment casting microstructures; single crystals; superalloys